Organizational engineering in industry 4.0 - De la Fuente, David; Pino, Raúl; Ponte, Borja; Rosillo, Rafael (Lecture Notes in Management and Industrial Engineering, 2021)
The book includes the latest research advances and cutting-edge analyses of real case studies in the disciplines of Industrial Engineering and Operations Management from diverse international contexts. This work presents a revised version of the best papers presented at the XXIII International Conference on Industrial Engineering and Industrial Management promoted by ADINGOR (Asociación para el Desarrollo de la Ingeniería de Organización), which took place at the Polytechnic School of Engineering of Gijón (University of Oviedo), Asturias, Spain, from July 11th to 12th, 2019.